The Prevalence of Prostatic Cancer after Renal Transplantation - Mohammad Yazdani; Rahim Jorjani (مجله دانشکده پزشکی اصفهان, 2011)
Background: This study aimed to evaluate the prevalence of prostatic cancer after renal transplantation and its correlation with underlying etiology of renal failure, immunosuppressive compounds, and renal function after transplantation in comparison with normal population. Methods: In this cross-sectional study, 185 male renal transplant recipients, aged more than 40 years were entered. They were evaluated by digital rectal examination and free and total Prostat-specific antigene (PSA) levels were measured for them. They would have undergone prostatic biopsy under trans-rectal-ultrasonography if they had suspicious digital rectal examination, total PSA > 2.1 ng/ml or free/total PSA ≤ 0.15. Finding: None of patients had the criteria of prostatic biopsy. The mean age of patients was 56.2 ± 8.9 years and the largest age group was 50-59. The mean of PSA level was 0.88 ± 0.48 ng/ml; the minimum and maximum were 0.1 and 2 ng/ml, respectively. The mean, minimum, and maximum of free/total PSA were 0.46 ± 0.22, 0.2, and 1 respectively. Conclusion: In this study, none of patients were candidate for prostatic biopsy. Prolonged studies with regular follow-up are recommended.